Sport as Therapy - Schütz K (Dynamic Media Sales Verlag, 2021)
Problem: The aim of the study was to investigate the experience of equestrians during the Corona disease, as they have not yet been the focus of research in this context.Methods: Disease-related guidelines on riders were analyzed, considering the constructs of restrictions and renunciation as well as the experience of worries in the respective riding stables and in dealing with the horses. To this end, 813 equestrians from Germany and Austria in particular were questioned online.Result: Horse owners experienced the requirements as more restrictive compared to riding participations; there were no differences in the experience of worries. People from riding stables where the disease-related requirements were adhered to experience the associated renunciation and restrictions more strongly compared to those from riding stables where the requirements were not adhered to. In stables with fewer horse boxes, people experienced the situation as less restrictive compared to stables with more boxes. Riders from Austria showed higher values for the constructs renunciation / restrictions and worries than German riders. Since the outbreak of the disease, equestrians stayed in the stables for a shorter time than before.Discussion: Results show that the Corona disease affects equine athletes differently in different areas, with much more research needed on the broader effects also including other Sports.Key Words:Psychological Well-Being, Equestrian Sport, Mental Strength, Experience, Crisis